The reactions of dimethyl carbonate and its derivatives. Issue 1 (14th November 2017) - Tundo, P.; Musolino, M.; Aricò, F.
Abstract : The worldwide urge to embrace a sustainable and bio-compatible chemistry has led industry and academia to develop chlorine-free methodologies focused on the use of CO2 -based compounds, such as dimethyl carbonate, as feedstocks, promoters and reaction media. Abstract : The worldwide urge to embrace a sustainable and bio-compatible chemistry has led industry and academia to develop of chlorine-free methodologies focused on the use of CO2 and CO2 -based compounds as feedstocks, promoters and reaction media. In this scenario, dialkyl carbonates (DACs) and in particular dimethyl carbonate (DMC) occupy a privileged position due to their low toxicity, high biodegradability and peculiar reactivity. Nowadays, the large-scale production of DACs is carried out through clean processes ( i.e., phosgene-free processes), which include the direct insertion of CO2 into epoxides, allowing – in principle – recycling of the carbon dioxide emitted during carbonate degradation. This groundbreaking achievement has definitely drawn attention toward the conception of procedures to activate the rather stable DACs with the aim of employing these compounds as green alternatives to their reactive chlorinated analogues. DACs are ambident electrophiles, which under appropriate conditions can undergo BAc 2- or BAl 2-nucleophilic substitution to give, respectively, alkoxycarbonylation and alkylation reactions. The many efforts devoted to improving the industrial suitability of organic carbonates have unveiled an intriguing and innovative chemistry as demonstrated by the numerous publications and patents published on these compounds over the last thirty years. This review reports on DACs as alkoxycarbonylating agents and their applications in industry and fine synthesis, as well as alkylating agents including allylic alkylation using palladium catalysts and the Pd/Ti bimetallic system and anchimerically driven alkylations via mustard carbonates. Moreover, the reactivity of organic carbonates toward several substrates and under different reaction conditions is described along with some distinctive DAC-mediated cyclization and transposition reactions. The synthesis of olefins and ethers under both liquid and gas phase conditions via thermal decarboxylation of organic carbonates is also reported.